ATC-based task allocation in virtual enterprise. (31st January 2011) - Ling, Liuyi; Liang, Liang; Gou, Qinglong; Du, Shaofu
A virtual enterprise (VE) consists of several autonomous and heterogeneous member enterprises (MEs) that move towards their own objectives. In order to improve its efficiency and responsiveness, the VE has to effectively synchronise and integrate business components that are distributed across the MEs. This paper probes task allocation problem in a virtual enterprise. ATC (Analytical Target Cascading) is used to coordinate the production task allocation in order to achieve the optimal solution with high customer satisfaction and low total production cost. The numerical study in this paper demonstrates that ATC is an effective coordination method.